Review—Surface-Enhanced Raman Scattering Sensors for Food Safety and Environmental Monitoring. Issue 8 (21st April 2018) - Tang, Haibin; Zhu, Chuhong; Meng, Guowen; Wu, Nianqiang
Abstract : This article gives a review of surface-enhanced Raman scattering (SERS) sensors for food safety and environmental pollution monitoring. It introduces the basic concepts of SERS substrates, SERS enhancement factors and mechanisms, SERS probes/labels, molecular recognition elements as well as optofluidic SERS devices (SERS sensors integrated with microfluidics). This article places an emphasis on the design strategies of various SERS sensors by utilizing fingerprinting SERS spectra or by using SERS probes. It highlights the applications of SERS sensors in detection of heavy metals (such as Hg 2+, Pb 2+, Cd 2+ and As 3+ ), inorganic anions (nitrite, nitrate, perchlorate and fluoride), toxic small molecules (polycyclic aromatic hydrocarbon, polychlorinated biphenyls, herbicides, pesticides, antibiotics and food additives), as well as pathogens (bacteria and viruses).